Youth engagement in livestock production and marketing in East Africa - Bullock, Renee; Auma, Joseph; Baltenweck, Isabelle; Dione, Michel M.; Okeyo Mwai, Ally; Ndiwa, Nicholas N.; Omore, Amos O.; Ouma, Emily A.; Yami, M. (SAGE Publications, 2023)
There is limited empirical evidence about how youth engage in livestock production in East Africa. The primary objective of this article is to better understand youth engagement in the livestock sector, namely commercialization and marketing. We compare youth to non-youth in four areas: livestock asset ownership, access to and use of services and improved practices and lastly, market participation. Our framework draws upon agricultural transformation concepts to suggest a tentative pathway through which livestock can support youth in transitions. We draw upon quantitative data and analyze and compare youth to nonyouth in intensive and extensive livestock systems in Kenya, Uganda, Ethiopia, and Tanzania and investigate four livestock systems, dairy, extensive ruminants, pig, and chicken systems. The results showed that there were no systematic youth-specific trends across the asset ownership, levels of commercialization or market participation. Also, low asset ownership did not generate observable youth specific differences in market participation. Rather, education and improved practices correlate with higher levels of market participation. Exploring how livestock are acquired and implications upon asset-based approaches is recommended to better understand the potential of livestock as a source of income during youth transitions in different livestock systems. More evidence is needed to inform and tailor policy approaches to support equitable opportunities in the livestock sector better. Research into understanding how social factors, including gender, shape youth opportunities and constraints, is needed.